Bracelet Making for the Development of Creativity and Fine Motor Skills in Children at Subang Mewah Cultural Center, Kuala Lumpur, Malaysia - Muhammad Supawi; Khairunnisa Khairunnisa; Jamilah Jamilah (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This research explores the impact of bracelet-making activities on children's development at the Subang Mewah Children’s Center, Malaysia. The study focuses on the development of creativity, fine motor skills, social interaction, and self-confidence among children, particularly those from migrant communities. The research aims to understand how these activities contribute to children's cognitive and emotional growth. Using qualitative methods, including observation and interviews with teachers and children, the study evaluates the effectiveness of bracelet-making as a tool for development. The main findings reveal that bracelet-making allows children to express creativity through design, improves fine motor coordination, fosters collaboration and communication, and enhances self-esteem. Children not only learn technical skills but also develop social abilities by working together and helping each other. Completing a creative project boosts their confidence, encouraging them to face new challenges. The research concludes that creative activities like bracelet-making are valuable tools in non-formal educational settings, promoting holistic development in children. The study suggests that integrating such activities can be an effective way to support migrant children’s growth and social integration. Future studies could explore incorporating digital tools into these activities to further enhance learning experiences.